Community-associated methicillin-resistant Staphylococcus aureus (CA-MRSA) clones from Paraguayan children - Rodríguez, Fátima (2020)
Introduction: Staphylococcus aureus is considered one of the most important human pathogens, and its levels of resistance to methicillin have increased even in strains isolated from people without nosocomial risk factors. Molecular analysis is essential for understanding the patterns of dissemination. The objective of this study was to identify community-acquired methicillin-resistant S. aureus (CA-MRSA) clones that infected Paraguayan children patients in two periods of time. Methodology: An observational, descriptive study was designed to determine the genetic variability of 115 isolates of CA-MRSA recovered from children who attended four reference centers in Paraguay between 2009-2010 and 2012-2013. Results: The combined use of Pulsed Field Gel Electrophoresis (PFGE), Multi-Locus Sequencing Typing, Multi-Locus Variable Analysis (MLVA) and Spa typing techniques allowed the identification of two dominant clones: ST30-IV-t019 (77%) and ST5-IV-t311 (10%), and the establishment of the former as the leading cause of CA-MRSA infections in children during the study period. Conclusions: This is the first study that provides epidemiological information as well as microbiological and molecular characteristics of CA-MRSA isolates recovered from children from Asunción and the Central Department of Paraguay.